The Effect of pH to Drying Process of Colloidal Silica Using Flame Spray Combusto - Sugeng Winardi; A. Y. Retnaningtyas; R. R. Hidayat; Lailatul Qomariyah; Widiyastuti Widiyastuti; Kusdianto Kusdianto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Spray drying widely applied in industry for drying the material because it has many advantages including capable to produce particle up to nanometer size, having a continuous process, and high purity. The method that we used in this research is Flame Spray Combustor. This research has the objective to synthesize particles of silica from waterglass and determine the effect of pH on particle silica produced. Analysis of SEM, XRD, and BET was conducted to determine the morphology, crystallinity, particle’s size, surface area and pore size of the silica particles produced. Morphology of silica is small spherical and has an amorphous structure. At pH 8 to 10 the size of silica particles increases with increasing pH, and at pH 11 the size decreases. The higher pH, the smaller surface area of silica particles produced. Meanwhile, the greater pH, the greater pore size of silica particles produced.